KELULUSHIDUPAN DAN PERTUMBUHAN IKAN TAPAH (Wallago leeri) DENGAN FREKUENSI PEMBERIAN PAKAN YANG BERBEDA - Seftian Andi Anggara; Usman M. Tang; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on June-August 2015 in Hatchery on Jl.TamanKarya, Pekanbaru-Riau Province. The aim of research was determine the effect ofdifferent feeding frequency on survival and growth of Wallago leeri In this research, 3treatments with 3 replications was applied. Fish used in this research were 10 to 15 cmin length. Stocking density of fish was 70 fish/m3. Fish meal frequency applied was 2, 3and 4 times/day. Fish diet used in the research was trash fish . Based on Anova analysis,results showed that the fish meal distribution of 4 times/day gave the best result on dailyweight growth of 1,86 g, absolute length growth 3,70 cm survival rate of 100 %. andfish diet efficiency 58,21%Keywords : Food Frequency,Wallago leeri Growth, survival